2021
DOI: 10.1093/mmy/myab055
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of polyunsaturated fatty acids alone or in combination with fluconazole on Candida krusei biofilms in vitro and in Caenorhabditis elegans

Abstract: The incidence of infections by non-albicans Candida species, including Candida krusei, is increasing. Candida krusei exhibits intrinsic resistance to fluconazole and rapidly develops acquired resistance to other antifungals. Moreover, this yeast can form biofilm with increased resistance. Hence, there is a need to develop novel therapeutic strategies to combat infections caused by this pathogen. One such approach is through combination therapy with natural compounds, such as polyunsaturated fatty acids (PUFAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…The biofilm inhibition rates (%) ranged from 20.52% to 80.99% (LOA < ALA < AA <EPA < DHA < GLA) ( Table S1 ). A recent study by Jamiu et al 20 also demonstrated LOA and GLA displayed significant inhibition of C. krusei biofilms. Both increased the susceptibility of C. krusei biofilm to fluconazole via induction of oxidative stress, cell membrane damage, and disruption of efflux pump activity.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The biofilm inhibition rates (%) ranged from 20.52% to 80.99% (LOA < ALA < AA <EPA < DHA < GLA) ( Table S1 ). A recent study by Jamiu et al 20 also demonstrated LOA and GLA displayed significant inhibition of C. krusei biofilms. Both increased the susceptibility of C. krusei biofilm to fluconazole via induction of oxidative stress, cell membrane damage, and disruption of efflux pump activity.…”
Section: Discussionmentioning
confidence: 82%
“…and have recently been considered potential alternative antifungal agents. [17][18][19][20][21][22] Nevertheless, few published studies have investigated the activities of essential fatty acids (EFAs) on biofilms in the formation and mature stages of clinical C. albicans isolates. EFAs, which are types of polyunsaturated fatty acids (PUFAs), cannot be synthesized by the human body and must be obtained in the diet.…”
Section: Introductionmentioning
confidence: 99%
“…Among the Candida species, Candida albicans is the most common pathogen, however, recently non- albicans Candida infections are increasing [ 3 ]. Especially, C. krusei has intrinsic resistance against fluconazole and low susceptibility to amphotericin B and flucytosine, at the same time, it develops acquired resistance to other antifungals enhanced by its ability to form biofilm [ 3 , 12 , 13 ]. Moreover, the yeast has lowest 90-day survival rate when compared to other systemic Candida species infections [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, osteomyelitis of foot bones is limited to only 3% of all Candida osteomyelitis cases, as reported by Slenker et al [ 2 ]. The organism spreads by predominantly hematogenous route, direct inoculation and, rarely, by contiguous manner, and Candida albicans was identified in 65% of cases, although non- albicans Candidal infection is increasingly reported [ 3 ]. Albeit intact neutrophil function is critical to defense against Candida infection, surprisingly, less than 20% of all cases were associated with significant immunosuppression such as neutropenia, organ/bone marrow transplantation, underlying hematologic malignancy and others.…”
Section: Introductionmentioning
confidence: 99%
“…Another flavonoid, kaempferol, could downregulate CDR1 and CDR2 genes in fluconazole-resistant C. albicans [ 99 ]. Berberine hydrochloride, traditional Chinese medicine with antimicrobial effects, reduces intracellular efflux of fluconazole by downregulating CDR1 [ 100 ], while polyunsaturated fatty acids could reduce efflux from C. krusei cells [ 101 ]. Benzoxazole derivatives could interfere with both cell efflux and ergosterol synthesis in C. albicans [ 62 ].…”
Section: Recent Update On Antifungal Targets and Strategiesmentioning
confidence: 99%